Ideational factors and parenthood. A gender-and paritiy specific analysis in a post-communist society - Zsolt Sped́er; Balaźs Kapitańy (Hungarian Demographic Research Institute, 2009)
Our analysis aims at analyzing whether general values and familial attitudes had a role in becoming parent and in bearing a second or a third child in the post-communist society of Hungary experiencing a demographic transition. This analysis is all the more timely as cultural and ideational explanations play a very important role in the interpretation of recent demographic changes and also because excellent analytical opportunities are offered by the first two waves of a panel survey. The effects of religiosity, individualism- and anomie-scale, optimism, age norms, ideal number of children and gender roles are analyzed. Using parallel logistic regression models for male and female on the one side, and first and further births on the other side, we could show and compare gender- and parity-specific influences of ideational factors. The analysis will not allow us to test general theories of demographic transition, but enables collect arguments for their relevance.
Keywords: J13; 300; Reproductive behaviour; fertility determinants; attitude; value orientation; gender differences; post-communist demographic transition; follow-up survey; Generation and Gender Program; Sozialer Wandel; Welt; Bewertung; Meinung; Bulgarien